(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
This article addresses a complex philosophical problem – the problem of antinomy, which is associated with the dialectical nature of the cognition process. In the works of F. M. Dostoevsky there is an antinomic, but it is not the defining creative principle of the writer. In the novel «Karamazov Brothers» the antonymous thought of Ivan Karamazov is considered with the rejection of God’s world, but the acceptance of the Creator. However, by not accepting of God’s world, human no longer accepts God, although he can assert the opposite. This division leads eventually to atheism, to theomachy and the spiritual death of the hero.